Relationship Between Knowledge And Family Support With Pregnant Women's Interest In Participating In Prenatal Yoga At Rsu Ummi Bengkulu In 2024 - Seftiani, Dwi; Situmorang, Ronalen Br; Saputri, Meitha Tria (Universitas Dehasen Bengkulu, 2025)
Prenatal yoga exercises for pregnancy can focus on the rhythm of breathing, prioritizing comfort and safety in practicing so it can provide many benefit to pregnant women (Ronalen, 2020). The purpose of this study was to determine whether there was a relationship between knowledge and family support with the interest of pregnant women in participating in prenatal yoga at RSU UMMI Bengkulu. The method in this study used a cross-sectional design. The population in this study were 298 pregnant women who underwent pregnancy check-ups at RSU UMMI, Bengkulu City in January 2024. The sample was taken using non-probability sampling with a purposive sampling approach with a sample size of 75 pregnant women. Data collection was obtained from distributing questionnaires and filling out checklists on respondents. The results of the study obtained : (1) almost half of the respondents 27 (36%) with low interest; (2) the majority of respondents (54.7%) pregnant women with less knowledge; (3) the majority of respondents (52.0%) pregnant women did not receive support; (4) There is a relationship between knowledge and the value of ρ value = 0.001; (5) There is a relationship between family support and the value of ρ value = 0.002. Researchers hope to be able to provide input to pregnant women about the importance of participating in prenatal yoga because it has many benefits for pregnant women where during pregnancy the mother and fetus are in a healthy condition and the delivery process is normal and smooth.